Why do Farmers Prefer Oil Palm? Lessons Learnt from Bungo District, Indonesia - Feintrenie, L.; Chong, W.K.; Levang, P. (2010)
Indonesia has been the world’s largest producer and exporter of palm oil since 2008. This paper discussed the livelihood impacts of oil palm development in Indonesia, based on lessons learnt from Bungo district, in the province of Jambi. The various community-company partnerships that structure the sector are reviewed and the difficulties raised by the joint ventures schemes are discussed. The merits and drawbacks of oil palm as a smallholder crop are then analysed, based on household socio-economic surveys conducted in 2007–2010. The main causes of conflicts between oil palm companies and communities are unclear land tenure, and a recurrent lack of leadership in smallholders’ cooperatives. Under fair partnerships between smallholders and companies, oil palm could become a smallholder friendly crop. The land-use profitability analysis demonstrates the high returns that can be generated by oil palm independent smallholdings, making it highly competitive with rubber, and much more profitable than rice production.